Promoting Family Wellness and Preventing Child Maltreatment : Fundamentals for Thinking and Action - Peirson, Leslea; Nelson, Geoffrey B. (Geoffrey Brian); Prilleltensky, Isaac, 1959- (Book collections on Project MUSE., 2001)
Deals with the promotion of emotional well-being in families, and the prevention of child maltreatment. Values, policies and resources are examined as both facilitators of, and barriers to, effective action.